International Conference on Use of ICT and ODL in Teacher Education : Bihar, India - World Bank (Washington, DC, 2014)
With Sarva Shiksha Abhiyan (SSA) transitioning towards the Right To Education (RTE), teacher education institutions and systems need to be fully geared up to meet the demands of pre-service and in-service teacher education and their ongoing professional development. Most states do not have adequate systems to provide the necessary cadres of trained elementary level school teachers. It is thus important to enhance the roles and capacities of teacher education institutions in India to support them to become globally competitive, professionally managed, and futuristically progressive to cater to the needs of huge back logs of untrained teachers. This training is crucial to ensure that children at the elementary levels get quality education in accordance with the National Curriculum Framework (NCF) 2005 and its basic tenets of child centered pedagogy.